Pengaruh Kegiatan Literasi Kampus Mengajar terhadap Hasil Belajar Siswa: Kajian Literatur - Najamudin Najamudin; Dwi Muliati; Siti Nuraliyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The low interest in reading and learning outcomes of students in Indonesia poses a significant challenge in the education sector. The Kampus Mengajar program has emerged as one of the solutions to enhance literacy and the quality of learning in schools. This article aims to analyze the impact of literacy activities initiated through the Kampus Mengajar program on student learning outcomes using a literature review approach. The research uses a qualitative method in the form of a literature review that examines various relevant sources published between 2020 and 2026. The study's findings indicate that structured literacy activities, such as reading for 15 minutes before lessons, have a significant impact on the improvement of students' cognitive, affective, and psychomotor skills. Literacy is not limited to reading and writing skills but also serves as a crucial foundation for developing critical thinking abilities, which are directly correlated with students' academic performance. Therefore, the Kampus Mengajar program can be an important driver to enhance reading interest and the quality of learning, as well as shape a more critical and high-achieving generation in the future.